Implementation Of Islamic Education Values In Building Students' Character In The Digital Era At SMP IC Darussalam - Asari, Erham; Amma, Tasurun; Maghfiroh, Ani (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
This research explored the integration of digital technology with Islamic-based character education. The main goal is to analyze how Islamic Religious Education values are applied to shape student character in the context of technological advances. The study focuses on the processes, strategies, and approaches used by teachers, as well as the challenges they face in integrating technology with religious education. Using a qualitative descriptive approach, data was collected through interviews, observations, and document analysis. The findings reveal that The study highlights the challenges faced by teachers, such as students' dependence on technology, exposure to inappropriate content, and limited teacher skills in using digital tools. To overcome these obstacles, strategies such as selective use of technology, supervision of digital content, teacher training, and direct integration of Islamic values into digital materials are implemented. The holistic approach ensures that Islamic character development is maintained, balancing religious education with technological advancements to prepare students for both the digital era and adherence to Islamic principles.